EVALUASI KONTRIBUSI DAN EFEKTIVITAS PAJAK DAERAH DAN RETRIBUSI DAERAH TERHADAP PENDAPATAN ASLI DAERAH KOTA SEMARANG TAHUN 2012 – 2016 - Rahmatya Widyaswati; Rosyati Rosyati; Nurul Juwariyah (Badan Perencanaan Pembangunan Daerah Kota Semarang, 2018)
City as a province that has embraced the regional autonomy sistem must be able to finance regional expenditures without relying on the central government. Locally-generated revenue, local tax, is a source of government revenue. Locally-generated revenue is reflecting of the economic independence of a region. Researchers are interested in testing the contribution and effectiveness of Local Taxes for locally-generated revenue for 2012-2016. The purpose of this study is to evaluate the contribution and effectiveness of local taxes on locally-generated revenue in Semarang. The steps taken in this study are : Calculating the percentage (%) growth rate of local taxes, Calculating and interpreting the level of effectiveness of local tax management. The data used in this study is secondary data obtained from the Semarang City Revenue Agency. Evaluation using effectiveness and contribution evaluation. The level of effectiveness of the Semarang City Local Tax is in the criteria of being very effective while the contribution of Local Taxes in the category is very less to less. For Effectiveness and contribution of Local Levies every year has decreased. Contributions for each Semarang city taxes post fall into the category of very less to less, ranging from less than 1% to above 15% of locally-generated revenue. The effectiveness of each Semarang city taxes post are in the very effective category (which ranges from more than 100). With the highest effectiveness 135.15% (2014) on BPHTB and the lowest 0% (2013) on Swallow Bird Nest Taxes. The contribution and effectiveness of local levies each year has decreased. For the local revenue of the Semarang City revenue agency, it cannot optimize because it only manages each agency.